Disease Activity and Maternal–fetal Outcomes in Pregnant Women With Prolactinoma: A Systematic Review and Meta-analysis - Bandeira, Diego Barata [UNESP]; Alves, Letícia Santana [UNESP]; Glezer, Andrea; Boguszewski, Cesar Luiz; Nogueira, Vania dos Santos Nunes [UNESP] (The Endocrine Society, 2025)
Context: Women with prolactinoma are usually infertile but can conceive after surgery or treatment with dopamine agonists. Objective: To evaluate the impact of pregnancy in prolactinoma's natural course and in maternal–fetal outcomes. Data Sources: MEDLINE, EMBASE, LILACS, and CENTRAL. Study Selection: Observational studies that included at least 3 pregnant women with prolactinoma. Data Extraction: Two independent reviewers selected studies, assessed the risk of bias, and extracted data from the included studies. Data Synthesis: Fifty-two studies were included, involving 2544 pregnancies in 1928 women. Stata Statistical Software 18 was used for proportional meta-analyses. The overall frequency of pregnant women on dopamine agonist treatment at conception was 97% and for either continuing or resuming treatment during pregnancy was 6%. The overall frequency of miscarriage was 10% (95% CI, 8-12), 3% for prematurity (95% CI, 2-5), 4% for symptomatic tumor growth during pregnancy (95% CI, 2-8), 4% for visual impairment (95% CI, 2-7), 6% for headache (95% CI, 4-9), and 4% for development of gestational diabetes (95% CI, 3-7). The overall frequency of congenital malformations was 2% (95% CI, 1-4), 2% for perinatal mortality (95% CI, 1-2), and 6% for low birth weight (95% CI, 3-9). Moreover, prolactinoma's size is a significant modifier for visual impairment. Conclusion: Pregnancy in women with prolactinoma is safe in relation to fetal and maternal outcomes with low frequencies of miscarriage, prematurity, symptomatic growth, visual impairment, headache, congenital malformations, perinatal mortality, and low birth weight.
Keywords: dopamine agonist; meta-analysis; pregnancy; prolactinoma; systematic review